A Link to the Past: Race, Lynchings, and the Passage of Stand-Your-Ground Laws. Issue 4 (2nd October 2021) - Dirlam, Jonathan; Steidley, Trent; Jacobs, David
ABSTRACT: What social and political factors explain the presence of Stand-Your-Ground (SYG) laws in US. states? This paper assesses the influence of crime and violence prevalence, minority threat theory, and self-help theory on SYG law adoption using discrete-time event-history analysis. Our findings indicate that these laws are linked to a violent vigilante and racially animus past. We also find evidence for minority threat theory with minority presence positively associated with SYG law adoption.